Perbandingan Penggunaan Agregat Halus Abu Batu Kayu Geritan Dan Pasir Weleri Terhadap Kuat Tekan Beton - Winanto, Rakha Wisam; Tisnawati, Tisnawati; Khamid, Abdul (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2024)
ABSTRACT Concrete is a building material used to support loads in building construction which is composed of cement, coarse aggregate, fine aggregate, water and additional materials if any. The fine aggregates used are stone ash, geritan wood and weleri sand. to find out how the compressive strength compares using the two fine aggregates. This research uses 5 variations of concrete types with each variation having 3 samples with the concrete quality plan being K225 or f'c 18.63 MPa, with a mixture of 100% stone ash, 75% stone ash and 25% weleri sand, 50% stone ash and 50% weleri sand, 25% stone ash and 75% weleri sand, and 100% weleri sand. The compressive strength obtained in this research is still in accordance with the planned compressive strength, whether using stone ash or weleri sand. For the use of 100% stone ash, the compressive strength of concrete aged 28 days is 24,179 MPa, while using weleri sand has a compressive strength of 23,106 MPa. So it can be concluded that the tensile strength using stone ash is higher than using weleri sand